Implementasi Penyertaan Akad Wakalah Dalam Pembiayaan Murabahah Pada PT. Bank Sumut KCPSy Panyabungan: Warisatul Ummi - Warisatul Ummi (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2025)
AbstractThe purpose of this study is to examine the implementation of the Wakalah agreement in Murabahah financing at Bank Sumut, Panyabungan Branch Office, and the level of customer understanding of the Murabahah and Wakalahagreements at PT. Bank Sumut, Panyabungan Branch Office. The research method used is field research with a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The results indicate that PT. Bank Sumut, Panyabungan Branch Office, always includes a complementary agreement, the Wakalah agreement, when distributing Murabahah financing. Murabahah financing at PT. Bank Sumut, Panyabungan Branch Office, meets the Wakalah requirements, thus fulfilling Sharia compliance standards and principles. Sharia compliance standards in Wakalah include adherence to the pillars and requirements of the Wakalah contract, adherence to fatwas and regulations, adherence to the Murabahah bil Wakalah process, documentation, and transparency. The application of the Wakalah contract in Murabahah financing at Bank Sumut KCPSy Panyabungan reflects both compliance with Sharia principles and transaction efficiency. However, customers at PT. Bank Sumut KCPSy Panyabungan have very little understanding of the contracts used, the financing proposed, and the role explained by the bank, which serves as a representative in purchasing goods. Keywords: Contract, Wakalah, Murabahah, Financing, Implementation